Current Research Status of Genetic Algorithm Research in China's Library Sector. - Yang, Guangyuan; Chen, Lei; Yu, Zhen; Yihei, Aniu (SHS Web of Conferences, 2023)
As an advanced technology of Data Mining, Genetic Algorithm provides an important method for deeply excavating library's collection resources and personalized interactive learning services. The paper adopts the method of bibliometrics to statistics, combing and analysis of the current research status of Genetic Algorithm research in China's Library Sector, finds the characteristics of Genetic Algorithm research in China's Library Sector, and proposes the research trends of Genetic Algorithm research in China's Library Sector in the future for promoting in-depth research and practice in the field of Genetic Algorithm research in China's Library Sector, and improves the utilization rate of library's collection resources and service effectiveness.